A reply to the remarks of Arthur Dobbs, Esq. [electronic resource] : on Capt. Middleton's vindication of his conduct on board His Majesty's ship the Furnace, when sent in search of a north-west passage, by Hudson's-Bay to the western American ocean, humbly inscribed to the Lords Commissioners for executing the office of Lord High Admiral of Great-Britain and Ireland, &c. - Middleton, Christopher, d. 1770. (London : Printed for George Brett, ., 1744)
Some text in double columns. Errata--p. [95-96]. Includes index. Electronic reproduction. Mode of access: Internet. 44